Analysing Peatland Subsidence in Pelalawan Regency, Riau Using DInSAR Method - Ruli Dwi Susanti; Ira Mutiara Anjasmara (IPTEK Journal of Proceedings Series, 2019)
Indonesia is known as a country that have the largest peatland in Southeast Asia. Peatland is often used in agricultural, plantation and settlement purposes. Before, peatland must be drained as one procedure of land clearing activity. However, an error during this process often comes and cause some problems such as drought, subsidence and even forest fire. A characteristic of peatland, irrewetable, making peatland is very hard to be wet after getting dry. This research is aiming to observe peatland subsidence in Pelalawan Regency, Riau using SAR data Sentinel 1-A. The method that we use is Differential Interferometry Synthetic Aperture Radar (DInSAR). Beside Sentinel 1-A, DEM STRTM is used to remove topographic effect. Temporal baseline in this research is about one year between two acquisition data. The first pair of data is acquired in June 2015 and June 2016. While the second pair of data is acquired in June 2016 and July 2017. By using two pass DInSAR method, the process will yield two images of Line of Sight (LOS) Displacement during each period. The first DInSAR (June 2015-June 2016) reveals that the highest subsidence that occur in peatland is about 109,113 mm and the highest uplift is about 108,089 mm. The second DInSAR (June 2016-July 2017) reveals that the highest peat subsidence is about 251,842 mm and the highest uplift is about 73,715 mm.